Role of Molybdenum on the Electronic Properties of Passive Films on Stainless Steels. Issue 6 (27th March 2020) - Tranchida, G.; Di Franco, F.; Santamaria, M.
Abstract : Potentiostatic polarization of different stainless steel grades with a mirror surface finishing was performed in order to investigate the role of Mo on stainless steels corrosion behaviour. In the attempt to gain more insight into transpassive dissolution mechanism, passive films were grown in neutral aqueous solution (pH ∼ 7) at different polarizing potentials ranging from passive to transpassive conditions. According to the photoelectrochemical characterization, Cr dissolution occurs even at low polarizing potentials in the case of AISI 304L, while higher band gap values were obtained for passive films grown on austenitic 316L and duplex SSs. Capacitance measurements suggest that the flat band potential values estimated for passive films grown on austenitic 316L and duplex SS are more noble if compared to that of AISI 304L at all polarizing potentials. This is rationalized by considering that passive films on 316L and duplex are doped with Mo during film growth, changing their electronics properties (band gap and flat band potential) with a consequent shift to more positive value of the potential for chromate formation and dissolution.